Determinants of Taxpayer Ethical Behavior in Tax Avoidance and Evasion: Strategies for Mitigation - Arda, Devid Putra; Yusuf, Yusuf (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 19 No 2 (2024), 2024)
Research on tax avoidance and evasion in Indonesia and globally has produced inconsistent findings, raising concerns about their prevalence and ethical implications. This study explores the factors influencing taxpayer ethics and strategies to address tax avoidance and evasion through a systematic literature review. Analyzing 21 articles on tax avoidance, key determinants include Corporate Social Responsibility (CSR), Good Corporate Governance (GCG), profitability, and perceptions of the tax system, all of which significantly shape avoidance behavior. Similarly, 21 articles on tax evasion, including 18 focused on its determinants, highlight the roles of fairness perceptions, taxpayer knowledge, and law enforcement. Strategies to mitigate evasion emphasize GCG to enhance transparency and accountability, stronger law enforcement, and improved fairness to build trust and legal certainty. These findings offer valuable insights for policymakers and tax administrators, providing a foundation for developing effective compliance and enforcement strategies to reduce unethical tax practices. Keywords : tax avoidance, tax evasion, determinant, strategies for overcoming